Association of different antiplatelet therapies with mortality after primary percutaneous coronary intervention. Issue 20 (2nd February 2018) - Olier, Ivan; Sirker, Alex; Hildick-Smith, David J R; Kinnaird, Tim; Ludman, Peter; de Belder, Mark A; Baumbach, Andreas; Byrne, Jonathan; Rashid, Muhammad; Curzen, Nick; Mamas, Mamas A
Abstract : Objectives: Prasugrel and ticagrelor both reduce ischaemic endpoints in high-risk acute coronary syndromes, compared with clopidogrel. However, comparative outcomes of these two newer drugs in the context of primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) remains unclear. We sought to examine this question using the British Cardiovascular Interventional Society national database in patients undergoing primary PCI for STEMI. Methods: Data from January 2007 to December 2014 were used to compare use of P2Y12 antiplatelet drugs in primary PCI in >89 000 patients. Statistical modelling, involving propensity matching, multivariate logistic regression (MLR) and proportional hazards modelling, was used to study the association of different antiplatelet drug use with all-cause mortality. Results: In our main MLR analysis, prasugrel was associated with significantly lower mortality than clopidogrel at both 30 days (OR 0.87, 95% CI 0.78 to 0.97, P=0.014) and 1 year (OR 0.89, 95% CI 0.82 to 0.97, P=0.011) post PCI. Ticagrelor was not associated with any significant differences in mortality compared with clopidogrel at either 30 days (OR 1.07, 95% CI 0.95 to 1.21, P=0.237) or 1 year (OR 1.058, 95% CI 0.96 to 1.16, P=0.247). Finally, ticagrelor was associated with significantly higher mortality than prasugrel at both time points (30 days OR 1.22, 95% CI 1.03 to 1.44, P=0.020; 1 year OR 1.19 95% CI 1.04 to 1.35, P=0.01). Conclusions: In a cohort of over 89 000 patients undergoing primary PCI for STEMI in the UK, prasugrel is associated with a lower 30-day and 1-year mortality than clopidogrel and ticagrelor. Given that an adequately powered comparative randomised trial is unlikely to be performed, these data may have implications for routine care.